Virgin coconut oil as antioxidant and treatment on metabolic disorders: a short review - Ibrahim, Maizatul Akma; Ghazali, Nor Farahiyah; Mustafa, Farah Farisha; Tengku Muhammad, Tengku Sifzizul (Kuliyyah of Allied Health Sciences, International Islamic University Malaysia, 2020)
Coconut (Cocos nucifera) is among the most nutritious plant and has been used extensively as food and for various industrial purposes since thousand years ago. The coconut oil is remarkable for its nutritional value as it contains high nutrients, vitamins and minerals that are beneficial for human health. Conventional coconut oil is extracted through refining, bleaching and deodorizing (RBD) processes that has high tendency for contamination and requires extremely hot condition. This disfavored method leads to development of new wet method that produces purest form of coconut oil known as Virgin Coconut Oil (VCO). The present review aims to describe the nutritional and pharmacological benefits gained from the production of VCO. The review aims to summarize the scientific evidences to support folkfore claims that VCO could have higher nutritional value over the conventional coconut oil. The review covers the similarities in the pharmacological properties between the conventional and virgin coconut oil, as well as reveals number of pharmacological activities that are newly discovered to have more significant benefits for human health. This could be helpful for future researchers who are intending to investigate the plant nutritional and therapeutic potential to be incorporated in modern medicines sources.